Readers’ Perceptions and Expectations about Quality Services in Engineering University Libraries of Balochistan - Imran, Muhammad; Baqi, Abdul (Journal of Quranic and Social Studies, 2022)
The study intended to explore readers’ perceptions and expectations about quality of library services in engineering university libraries of Balochistan. In this the major focus related to reader`s perceptions and expectations is about service providing staff, facilities provided by the library as well as the accessing of information. University libraries have significant role in accomplishing overall institutional missions, the quality service cannot be provided without the understanding of reader needs and expectations. University libraries have essential role to satisfy the library reader needs and continues changes in technology readers expectations are increasing highly. This study is conducted using qualitative method; the questionnaire was developed on the bases of related literature, discussions with seniors and bases of previous studies to investigate the readers’ perceptions and expectations about quality services. The findings of the study revealed that insufficient space for group learning, less number of computer workstations, difficulties to access electronic databases, inadequate printed books, journals and IT infrastructure for speedy and easy services for readers.